CERF speaking tests: students’ take on career impact - Ch’ng, Looi-Chin; Gafar@Abd Ghaffar, Siti Zuraina; Arshad, Aqilah; Mahmud, Nur Farah Fadhliah; Sahari, Siti Huzaimah (Universiti Teknologi MARA, Sabah, 2025)
The Common European Framework of Reference for Languages (CEFR) serves as a key standard for assessing language proficiency, providing a structured and uniform evaluation system. This study explores ESL students’ perspectives on the significance of CEFR-aligned speaking tests. Data were gathered from 105 diploma students at UiTM Sarawak and UiTM Melaka through an online questionnaire. The results indicate strong student support for incorporating CEFR scores in academic settings, recognizing its effectiveness in highlighting language strengths and weaknesses. However, students perceived its relevance to employers as considerably lower, suggesting that CEFR is valued more for academic purposes than for professional use. This disconnect underscores the need to bridge the gap between academic assessments and industry expectations. Overall, the study emphasizes the value of CEFR-based assessments for both students and educational institutions while proposing ways to enhance their applicability in the job market.